2006
DOI: 10.1007/s11628-006-0010-y
|View full text |Cite
|
Sign up to set email alerts
|

The benefits of e-business adoption: an empirical study of Swedish SMEs

Abstract: The global nature of business today and the advances in information and communications technologies have compelled corporations to employ emerging technologies in order to remain competitive. In recent years electronic business has been adopted by many corporations to improve operational efficiency, profitability, and to strengthen their competitive position. This study examines the impact of web-based e-business on the small and medium-size enterprises (SMEs) in Sweden. The analyses of data collected for this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 13 publications
(13 reference statements)
1
13
0
Order By: Relevance
“…However, those respondents that were between the age group 40-49 years (mean=3.79) and 50 years and over (mean=3.63) differed from their counterparts that were in the age group, under 30 years in terms of the ease of use of e-marketing tools. These findings are consistent with Beheshti and Sangari (2007) who contend that inertia and resistance to Internet technology change is highest among older SME managers and owners. It therefore seems that younger owners/managers of SMEs are more prone to adopt e-marketing tools compared to their older counterparts.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…However, those respondents that were between the age group 40-49 years (mean=3.79) and 50 years and over (mean=3.63) differed from their counterparts that were in the age group, under 30 years in terms of the ease of use of e-marketing tools. These findings are consistent with Beheshti and Sangari (2007) who contend that inertia and resistance to Internet technology change is highest among older SME managers and owners. It therefore seems that younger owners/managers of SMEs are more prone to adopt e-marketing tools compared to their older counterparts.…”
Section: Discussionsupporting
confidence: 89%
“…This theoretical review culminated into the design of a self-administered questionnaire based on the adapted technology adoption scales used by Davies et al (1989) and Chau (1996). These scales were further validated within the context of e-business adoption among firms in the studies of Pearson and Grandon (2004); Beheshti and Sangari (2007) and Parker and Castleman (2009). The questionnaire was divided into three sections, namely; A, B, and C. Section A of the questionnaire primarily obtained demographic information from the respondents.…”
Section: Instrumentation and Data Collectionmentioning
confidence: 99%
“…It was furthermore proved that e-commerce is more beneficial to the service industry than to the manufacturing industry, and that smaller firms are the ones to benefit the most from the e-commerce investment. The research on the influence that web-based e-commerce of small and medium firms in Sweden has on firm performance has shown that there are benefits of e-business implementation in both operational and performance areas of firms [41]. The research shows a positive overall impact of e-business on these firms, and that investing in e-business technology has been beneficial to both manufacturing and service firms.…”
Section: Literature Review and Hypothesesmentioning
confidence: 96%
“…On the other hand, studies in e.g. the UK, Sweden, and New Zealand, [15,16,21] respectively, have shown that SME's are not a homogeneous group but vary greatly both in e-Business use as well as in the factors that influence them in adopting or rejecting e-Business technology. Moreover, these factors do not necessarily reflect the companies' business strategy or objectives any way, but may relate to e.g.…”
Section: Related Researchmentioning
confidence: 99%